Milestones from the Roman Road Drinjača – Sarajevsko Polje - Popović, Goran D. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Roman communication which connected the valley of the Drinjača river to Sarajevsko polje was very important during the mid III century. Many milestones from this communication testify to this. There are 30 discovered milestones in total on this communication, 12 of which are epigraphic. At the time of discovery, most of the milestones were in situ. The oldest of all milestones was from the period of Philip I reign (Marcus Julius Philippus) between 244 and 249, while the youngest one was built in honour of Marcus Claudius Tacitus, at the end of 275 or in the first half of the year 276. The milestones from this communication did not mark a reconstruction of communication, as it was believed earlier. At the time of very frequent changes on the throne, during the mid III century, the milestones gained honorary character. Their function was to express loyalty to the monarch.